The utility of point-of-care ultrasound in critical care nephrology - Passos, Rogério da Hora; Flato, Uri Adrian Prync; Sanches, Paula Rodrigues; Pellegrino, Carolina Moraes; Cordioli, Ricardo Luiz; Silva, Bruno Caldin; Campos, Felipe Galdino; Barros, Dalton de Souza; Coelho, Fernanda Oliveira; Bravim, Bruno de Arruda; Corrêa, Thiago Domingos (Frontiers in Nephrology, 2024)
Point-of-care ultrasonography (POCUS) is gaining heightened significance in critical care settings as it allows for quick decision-making at the bedside. While computerized tomography is still considered the standard imaging modality for many diseases, the risks and delays associated with transferring a critically ill patient out of the intensive care unit (ICU) have prompted physicians to explore alternative tools. Ultrasound guidance has increased the safety of invasive procedures in the ICU, such as the placement of vascular catheters and drainage of collections. Ultrasonography is now seen as an extension of the clinical examination, providing quick answers for rapidly deteriorating patients in the ICU. The field of nephrology is increasingly acknowledging the value of diagnostic point-of-care ultrasound (POCUS). By employing multi-organ POCUS, nephrologists can address specific queries that arise during the diagnosis and treatment of patients with acute kidney injury. This approach aids in ruling out hydronephrosis and offers immediate information on hemodynamics, thereby consolidating patient data and facilitating the development of personalized treatment strategies.